Fitment Assistance and Training For Practices “Sedentary Lifestyle” - Gumilar Mulya; Resty Agustryani; Anggi Setia Lengkana; Mega Widya Putri (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2023)
T The purpose of this community service activity is to introduce and provide assistance in efforts to improve physical fitness and design a fitness program for PJOK teachers so that later they can implement it in physical education learning in schools. After analyzing the situation, several problems were identified as follows: (1) There are still PJOK teachers who are not optimal in delivering physical fitness-based physical education materials during the COVID-19 pandemic (2) There is still a lack of knowledge of PJOK teachers about how to form physical fitness programs for students. children, (3) There are still PJOK teachers who tend to focus more on giving assignments, giving monotonous material which causes students to get bored. Therefore, this workshop is a solution for PJOK teachers to try to open scientific horizons regarding physical fitness learning in physical education.